Adverse Effects Due to the Use of Upper Limbs Exoskeletons in the Work Environment: A Scoping Review - Omar Flor-Unda; Rafael Arcos-Reina; Susana Nunez-Nagy; Bernardo Alarcos (Biomimetics)
Both for design issues and for the study, analysis, and understanding of the interaction of workers with exoskeletons, the study of adverse effects provides criteria to improve the design of more efficient exoskeletons with better ergonomics and long-term usability. In this work, a scoping review was carried out on adverse effects due to the prolonged use of upper-limb exoskeletons, which have been evidenced in the scientific literature. The causes of the effects are described in terms of their impacts on the physiological, psychological, and technological aspects that affect the user. A scoping review of articles of the last ten years on negative effects of upper-extremity exoskeletons for industrial tasks was carried out following the guidelines of the PRISMA® methodology with three phases: formulation of questions, definition of scopes and exhaustive search in SCOPUS, Web of Science, Science Direct, Taylor & Francis, and PubMed. The selection was made by two review authors with a Cohen’s Kappa coefficient of 0.9530, indicating high agreement. The effectiveness of upper-limb exoskeletons depends on the environment and the task, so an adaptable ergonomic design, field validations, and standards are required to ensure their functionality and acceptance. Use of exoskeletons mainly activates the posterior deltoid and latissimus dorsi and reduces the activity of muscles such as the trapezius, pectoralis major, anterior and middle deltoids, biceps brachii, brachioradialis, and flexor carpi radialis.